Distinct Orogenic Processes in the South‐ and North‐Central Tien Shan From Receiver Functions. Issue 6 (11th March 2020) - Zhang, Bingfeng; Bao, Xuewei; Xu, Yixian
Abstract: Uplifting mechanisms for the Tien Shan, an active intracontinental orogenic belt, have been under debate for decades, a key issue being how the convergence has been accommodated at depth. Here we investigate the Moho structure across the Central Tien Shan by common‐conversion‐point imaging and H‐k‐c stacking of receiver functions from a dense array. The observed Moho exhibits distinct characteristics among subblocks. A southward‐dipping diffuse Moho is imaged in the South‐Central Tien Shan (SCTS), in contrast with the relatively flat and sharp Moho beneath the Tarim Basin. This feature along with the large Moho offset beneath the South‐Boundary Fault suggests that the shortening and thickening of the Tien Shan crust rather than the underthrusting of the Tarim Basin are responsible for the uplift of the SCTS. In the North‐Central Tien Shan, however, the imaged Moho doublet provides direct evidence for the underthrusting of the Kazakh Shield accommodating the convergence there. Plain Language Summary: The formation of the Tien Shan mountains, situated ~1, 500 km north of the plate boundary between India and Eurasia, has puzzled scientists for decades. Tectonic activities at depth could deform and thus leave footprints on subsurface interfaces such as the crust‐mantle boundary (Moho). In this study, we reveal distinct Moho structure in the southern and northern parts of the Central Tien Shan through analyses of seismic records, suggesting different mountain building processes in the two regions. The strong Tarim Basin to the south squeezes the weak South‐Central Tien Shan mass just as a wooden block squeezes plasticine. The Kazakh lower crust in the north, on the other hand, underthrusts beneath the North‐Central Tien Shan. The combined effects of the two processes lead to the rapid growth of the present‐day Tien Shan. Key Points: Detailed crustal structure beneath the Central Tien Shan is imaged, suggesting varying deformation processes perpendicular to its strike The shortening and thickening of the Tien Shan crust are responsible for the high elevations in the South‐Central Tien Shan The underthrusting of the Kazakh Shield beneath the North‐Central Tien Shan accommodates the convergence there